Enhancing Sample-Efficiency in Reinforcement Learning Agents through Symbolic Reasoning - Shukla, Yash (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Computer Science.; Advisor: Jivko Sinapov.; Committee: Elaine Short, Reuth Mirsky, Chris Rogers, and Shiqi Zhang.; Keywords: Artificial intelligence, and Robotics.